(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
تعتبر ظاهرة الإنجاب في المجتمع من أكثر الظواهر الديموغرافية أهمية لما لها من تأثيرات كبيرة على حياة الأفراد والأسر، وإن مصطلح خصوبة السكان هو المصطلح الذي يطلق للدلالة على هذه الظاهرة وفي أي مجتمع سكاني، إلا أنه ينبغي التمييز بين الخصوبة والخصوبة الزواجية في المجتمع المدروس ليتم التعبير بشكل أكثر دقة عن خصوبة ذلك المجتمع، وبناءً على ذلك سيتم في هذا البحث إلقاء الضوء على ظاهرتي الخصوبة والخصوبة الزواجية في سورية ودراسة التباين والاختلاف في معدلاتهما على مستوى المحافظات السورية ثم على مستوى ريف وحضر تلك المحافظات، معتمدين في دراستنا هذه على أسلوب العرض البياني للبيانات المستخرجة من التعداد السكاني لعام 2004 باعتباره آخر تعداد تم للسكان على مستوى المحافظات السورية، ومن أهم النتائج التي تم التوصل إليها في بحثنا هي ارتفاع معدلات الخصوبة الزواجية عن معدلات الخصوبة في أغلب المحافظات السورية وفي ريف وحضر تلك المحافظات وذلك في جميع فئاتها العمرية. The phenomenon of procreation is considered one of the most demographical phenomena for it has huge effects on the life of individuals and families. The term "population fertility" refers to this phenomenon in any community but we should distinguish between the term "fertility" and "marital fertility" in the studied community to be expressed more accurately than the term "fertility" in that community. Depending on this, this research will focus on both fertility and marital fertility phenomenon in Syria and will study the Varity and differences in its rates on the level of these Syrian cities then on the level of urbanite and country of these Syrian cities depending in our study on the illustrative show of the extracted data from the population of 2004 as it is considered the last poll about population on the level of Syrian cities. Finally, one of the most important results of our research is the rising of marital fertility rates to fertility rates in most of the Syrian cities and in the urbanite and country of these cities in all its age groups.